A flexible pressure sensor based on rGO/polyaniline wrapped sponge with tunable sensitivity for human motion detection. Issue 21 (18th May 2018) - Ge, Gang; Cai, Yichen; Dong, Qiuchun; Zhang, Yizhou; Shao, Jinjun; Huang, Wei; Dong, Xiaochen
Abstract : High-performance stretchable and wearable electronic skins (E-skins) with high sensitivity and a large sensing range are urgently required with the rapid development of the Internet of things and artificial intelligence. Abstract : High-performance stretchable and wearable electronic skins (E-skins) with high sensitivity and a large sensing range are urgently required with the rapid development of the Internet of things and artificial intelligence. Herein, a reduced graphene oxide (rGO)/polyaniline wrapped sponge is prepared via rGO coating and the in situ synthesis of polyaniline nanowires (PANI NWs) on the backbones of sponge for the fabrication of pressure sensors. From the as-prepared flexible sensor, tunable sensitivity (0.042 to 0.152 kPa −1 ), wide working range (0–27 kPa), fast response (∼96 ms), high current output (∼300 μA at 1 V), frequency-dependent performance reliable repeatability (∼9000 cycle) and stable signal waveform output can be readily obtained. In addition to tiny physiological activities (voice recognition, swallowing, mouth opening, blowing and breath), robust human motions (finger bending, elbow movement and knee squatting–arising) can also be detected in real-time by the flexible sensors based on rGO/polyaniline wrapped sponge. All the results demonstrate that the flexible pressure sensor based on the functional-sponge is a promising candidate for healthcare monitoring and wearable circuitry in artificial intelligence.